Investigation of inhibition performance of kinetic hydrates inhibitors - Wang, Shuo (Curtin University, 2012)
The aim of this thesis is to investigate the inhibition process of tetrahydrofuran (THF) hydrates in presence of two kinetic hydrate inhibitors (KHIs), poly(N-vinylcaprolactam) and poly(vinylcaprolactam /vinylpyrrolidone/ dimethylaminoethyl methacrylate), and the effect of these KHIs on the formation and growth of THF hydrates at various experimental conditions, using a ball-stop rig and a rheometer. Other chemicals, including ethanol, ethylene glycol, and sodium chloride salt were used to investigate their synergic effect to the KHIs.